2012
DOI: 10.1371/journal.pone.0035900
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of JC Virus in Chinese Patients with Colorectal Cancer

Abstract: BackgroundJCV is a DNA polyomavirus very well adapted to humans. Although JCV DNA has been detected in colorectal cancers (CRC), the association between JCV and CRC remains controversial. In China, the presence of JCV infection in CRC patients has not been reported. Here, we investigated JCV infection and viral DNA load in Chinese CRC patients and to determine whether the JCV DNA in peripheral blood (PB) can be used as a diagnostic marker for JCV-related CRC.Methodology/Principal FindingsTumor tissues, non-can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…With the exception of two large studies that examined blood samples from 729 and 386 patients, respectively, numbers of patients were generally low (median = 69). Among four studies comparing JCV DNA between tumor and adjacent noncancerous tissues, two studies reported a significantly higher prevalence of the virus in tumor tissues . In addition, Coelho et al also detected JCV DNA between 100 colorectal lesions (hyperplastic polyps, adenomas and adenocarcinomas) and 100 adjacent normal colorectal mucosae, which reported a significantly higher prevalence in colorectal lesions than normal controls (90% vs .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of two large studies that examined blood samples from 729 and 386 patients, respectively, numbers of patients were generally low (median = 69). Among four studies comparing JCV DNA between tumor and adjacent noncancerous tissues, two studies reported a significantly higher prevalence of the virus in tumor tissues . In addition, Coelho et al also detected JCV DNA between 100 colorectal lesions (hyperplastic polyps, adenomas and adenocarcinomas) and 100 adjacent normal colorectal mucosae, which reported a significantly higher prevalence in colorectal lesions than normal controls (90% vs .…”
Section: Resultsmentioning
confidence: 99%
“…Among three studies comparing seroprevelance of JCV between CRC cases and healthy controls, only one study by Mou et al in 2012 reported significantly elevated prevalence of JCV in CRC patients as compared with healthy controls (OR: 3.0, 95% CI :1.2–8.5). Besides, Mou et al also found a higher JCV prevalence in tissues of CRC patients when comparing to colorectal tissues from healthy controls (OR: 6.6, 95% CI: 2.9–14.9). However, a statistically difference of the JCV prevalence between CRC cases and healthy controls was not confirmed in any of the other studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjacent normal mucosa in 35 positive colon adenocarcinoma specimens, and normal mucosa from six patients of the control group, had low viral loads 50-450 copies/µg DNA 76. Interestingly, PCR without adjustment with topoisomerase 77 showed statistically higher number of JCV copies in cancer than in non-cancerous tissues with a much higher relative number of copies/µg of DNA (49.1 to 10.3x10 4 in cancer tissue compared to 9-20x 10 3 in Theodoropoulos's study).…”
Section: Human Polyoma Viruses (Jc Virus)mentioning
confidence: 98%
“…An association between JC virus (JCV) and colorectal cancers (CRC) is known [175,176]. JCV encodes a gene expressing T-antigen, which is detected in the majority of CRC patients with positive family history [177].…”
Section: Prospects In Cancer Immunotherapymentioning
confidence: 99%